2013
DOI: 10.1136/jech-2013-203126.133
|View full text |Cite
|
Sign up to set email alerts
|

PP34 Interventions to Promote Informed Consent for Invasive Healthcare Procedures: A Cochrane Systematic Review and Meta-Analysis

Abstract: Background Informed consent is required before any surgery or invasive procedure is performed. Achieving ethically valid informed consent can be difficult: too little information may leave patients poorly informed and too much information may be overwhelming. As such interventions to promote information provision for informed consent are warranted. This study aimed to evaluate the impact of such interventions on a range of outcomes including patient knowledge, anxiety, and satisfaction. Methods Medical datab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…However, the review was limited by the large amount of heterogeneity in the outcomes used to determine the effect of the decision aids in the consent process. Similarly, a Cochrane review of interventions to promote informed consent for invasive procedures concluded that interventions to improve consent consistently improved patient knowledge [ 8 ]. However, although knowledge is clearly an important step in achieving informed consent, the authors of the review found that the tremendous heterogeneity in outcomes measured and how they were recorded made comparisons between studies difficult.…”
Section: Introductionmentioning
confidence: 99%
“…However, the review was limited by the large amount of heterogeneity in the outcomes used to determine the effect of the decision aids in the consent process. Similarly, a Cochrane review of interventions to promote informed consent for invasive procedures concluded that interventions to improve consent consistently improved patient knowledge [ 8 ]. However, although knowledge is clearly an important step in achieving informed consent, the authors of the review found that the tremendous heterogeneity in outcomes measured and how they were recorded made comparisons between studies difficult.…”
Section: Introductionmentioning
confidence: 99%
“…However, this task can be delegated to the radiographers, especially where no intervention or invasive technique is required. Nevertheless, it should be notice that radiographers have limited time with the patient and might not have seen the patient before their arrival, making it hard for the patient to give consent on such short notice (5). Therefore, those involved in obtaining the consent form should have adequacy in terms of explaining the procedures in simple language that an ordinary can understand and give consent.…”
mentioning
confidence: 99%